2020
DOI: 10.3390/pharmaceutics12070622
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Doxorubicin from the Drug Delivery Formulation Composed of Single-Walled Carbon Nanotubes and Congo Red: A Molecular Dynamics Study and Dynamic Light Scattering Analysis

Abstract: The controlled delivery and release of drug molecules at specific targets increases the therapeutic efficacy of treatment. This paper presents a triple complex which is a new potential drug delivery system. Triple complex contains single-walled carbon nanotubes, Congo red, and doxorubicin. Nanotubes are built of a folded graphene layer providing a large surface for binding Congo red via “face-to-face” stacking which markedly increases the binding capacity of the carrier. Congo red is a compound that se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…The decrease in pH changed the structure and stability and ensured efficient drug release. Unfortunately, Congo red is not a biocompatible compound [ 38 ]. In this study, both FBS in the environmental media and relatively high NaHCO 3 concentrations in alginate microspheres enhance Dox release, reinforcing that these alginate microspheres are suitable for drug delivery in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in pH changed the structure and stability and ensured efficient drug release. Unfortunately, Congo red is not a biocompatible compound [ 38 ]. In this study, both FBS in the environmental media and relatively high NaHCO 3 concentrations in alginate microspheres enhance Dox release, reinforcing that these alginate microspheres are suitable for drug delivery in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the analysis of the CR-drug complex (using DOX as an example) was extended, based on the previously conducted research [8,34,35,39,40]. Attempts were also made to introduce co-micelles formed from Congo red bound to Dox into all analyzed proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, we can expect that this contribution is not decisive, since our earlier studies (also experimental), concerning interaction of DOX with carbon nanotubes, suggested that DOX binds to the surface of CNT weakly. Additionally, without a specific co-adsorbate (Congo Red molecule), the adsorption is unstable [33,34]. We can thus anticipate that the systems I2A and I4A can spontaneously release DOX at acidic pH.…”
Section: Intercalation Of Dox In Dna Chainsmentioning
confidence: 99%